An investigation into the teaching and learning of intonation to the 9th grade students at a secondary school in Thai Binh province = Nghiên cứu điều tra về việc dạy và học ngữ điệu đối với học sinh khối 9 ở một trường cấp 2 tại tỉnh Thái Bình. M.A Thesis Linquistics: 60 14 01 11 - Nguyễn, Thị Diễm (H.: University of Languages and International Studies, 2018)
42 tr.